2023
DOI: 10.1029/2023jf007153
|View full text |Cite
|
Sign up to set email alerts
|

Background Topography Affects the Degree of Three‐Dimensionality of Tidal Sand Waves

Janneke Krabbendam,
Abdel Nnafie,
Bas Borsje
et al.

Abstract: Offshore tidal sand waves on the sandy bed of shallow continental shelf seas are more three‐dimensional (3D) in some places than others, where 3D refers to a pattern that shows variations in three spatial directions. Such sand waves have crestlines that meander, split or merge. The degree of three‐dimensionality seems to vary especially when large‐scale bedforms, such as tidal sand banks, are present underneath the sand waves. Understanding this behavior is important for offshore activities, such as offshore w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 39 publications
0
1
0
Order By: Relevance
“…Trains of smaller secondary dunes, superimposed on large primary dunes, have been observed in rivers worldwide (Cisneros et al., 2020; Galeazzi et al., 2018; Zomer et al., 2021). Many methods, including flume experiments (Lee et al., 2021; Reesink et al., 2018), field data collection (De Ruijsscher et al., 2020; Zhang et al., 2022; Zheng et al., 2022), linear stability analysis (Colombini, 2004; Ogor, 2018), Geographic Information System methods (Cassol et al., 2021, 2022; Debese et al., 2016; Di Stefano & Mayer, 2018), and numerical models (Krabbendam et al., 2023; Lefebvre & Cisneros, 2023; Paarlberg et al., 2009; Thibaud et al., 2013), have been employed to study river dune morphology and dynamics. However, recent studies have indicated that dunes in the laboratory exhibit a steeper lee side angle compared to those observed under field conditions (de Lange et al., 2021; Kostaschuk & Venditti, 2019; Van der Mark et al., 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Trains of smaller secondary dunes, superimposed on large primary dunes, have been observed in rivers worldwide (Cisneros et al., 2020; Galeazzi et al., 2018; Zomer et al., 2021). Many methods, including flume experiments (Lee et al., 2021; Reesink et al., 2018), field data collection (De Ruijsscher et al., 2020; Zhang et al., 2022; Zheng et al., 2022), linear stability analysis (Colombini, 2004; Ogor, 2018), Geographic Information System methods (Cassol et al., 2021, 2022; Debese et al., 2016; Di Stefano & Mayer, 2018), and numerical models (Krabbendam et al., 2023; Lefebvre & Cisneros, 2023; Paarlberg et al., 2009; Thibaud et al., 2013), have been employed to study river dune morphology and dynamics. However, recent studies have indicated that dunes in the laboratory exhibit a steeper lee side angle compared to those observed under field conditions (de Lange et al., 2021; Kostaschuk & Venditti, 2019; Van der Mark et al., 2008).…”
Section: Introductionmentioning
confidence: 99%